Pleomorphic Adenoma of Palate: A Case Report - Shris, Nagendra; Mishra, Ravish; Yadav, Deepak; Kandel, Laxmi; Ali, Shahid; Pathak, Hemanta Raj (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Pleomorphic adenoma is one of the most common benign salivary gland tumor affecting the major salivary glands mainly parotid gland of approx. 80% but infrequently the minor salivary glands of palate of approx. 7%. Salivary gland tumors are rare accounting only 2–3% of tumors occurring in head and neck region. The majority of minor salivary gland tumors are malignant in nature. The most common sites for minor salivary gland where pleomorphic adenoma arises are the palates followed by lips and cheek. This case report presents a case of pleomorphic adenoma of minor salivary gland of palate treated successfully by wide surgical excision with 1 cm healthy margin with uninvolved anatomical barrier under general anesthesia.